m^2+5m+6=0

Simple and best practice solution for m^2+5m+6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m^2+5m+6=0 equation:


Simplifying
m2 + 5m + 6 = 0

Reorder the terms:
6 + 5m + m2 = 0

Solving
6 + 5m + m2 = 0

Solving for variable 'm'.

Factor a trinomial.
(3 + m)(2 + m) = 0

Subproblem 1

Set the factor '(3 + m)' equal to zero and attempt to solve: Simplifying 3 + m = 0 Solving 3 + m = 0 Move all terms containing m to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + m = 0 + -3 Combine like terms: 3 + -3 = 0 0 + m = 0 + -3 m = 0 + -3 Combine like terms: 0 + -3 = -3 m = -3 Simplifying m = -3

Subproblem 2

Set the factor '(2 + m)' equal to zero and attempt to solve: Simplifying 2 + m = 0 Solving 2 + m = 0 Move all terms containing m to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + m = 0 + -2 Combine like terms: 2 + -2 = 0 0 + m = 0 + -2 m = 0 + -2 Combine like terms: 0 + -2 = -2 m = -2 Simplifying m = -2

Solution

m = {-3, -2}

 

You can always share this solution

See similar equations:

| 5x^2+10x+5=180 | | 6(1+8x^3)=9 | | x^3+6x^2=4x+24 | | 5x^2-7x+2=0 | | 2x^2-11x+15=0 | | 4x^2=12x | | 8x^2=72x | | 2x^2-2=-5x-1 | | 0=3x^2-5x-9 | | 3x^2-6x+9=0 | | 3q^2+16=-19q | | (-2x^2+3y^3)+(6x-5)=0 | | 2x^2+6x+4=0 | | 2x^2-5x-75=0 | | 2x^2-10x+18=0 | | 9s^2+3s-20=x | | (x-1)(x^2-4)+2(x-1)(x+2)=(x-1)P | | 9x^2-4.5x-3.5=0 | | 6x^2-5x-14=0 | | x^4-7x-18=0 | | x^2-8x+18=0 | | x^2-8b+18=0 | | 30a^2+am-m^2=0 | | 30a^2+am-m^2=o | | 12s^2+11st-5t^2=0 | | 14x^2+11yx-15y^2=0 | | 3x^2+8=0 | | -2v^2-v+12=-3v^2+6v | | x^2+15x-64=0 | | 2x^2+8x-2=0 | | 12x^2-x-20=0 | | 5x^2+13x+6=0 | | x^3-12x^2+35x=0 | | x^3-13x^2+30x=0 | | 6x^2+17x-45=0 | | x^4-3x^2+1=0 | | 5x^2-5x-3= | | 3x^2-13x+14=0 | | 6x^2+x-c=(cx-1)(3x+2) | | X*x=x^2 | | 9c=c^2 | | 3x^2-12=0 | | 3x^2-8=0 | | x^2+6=6x^2-16 | | 16x^2-25=0 | | .66x^2-36=0 | | .66x^2-32=0 | | 2x^2+7x+3=0 | | 6x^2-47x=0 | | 3x^2-10x+3=0 | | 36x^2+6x-6=0 | | 2x^2-41=5 | | 2x^2-41=0 | | 1-25X^2=0 | | x^2-x+9=0 | | x^2-8x+7=0 | | (p+5)x^2+p=19+2p | | 12c^2+43c+35=0 | | 12c^2+43+35=0 | | x^2-x+6=0 | | x^2+4x-45=0 | | y=-3.1x^2+20x | | 4x^2+15x+9=0 | | x^3-25x=0 | | x^2+17x-3=7x-12 |

Equations solver categories